INCORPORATING THE EDPUZZLE INTERACTIVE VIDEO PLATFORM TO IMPROVE STUDENTS’ LISTENING ABILITY - Nursyanti, Nursyanti; Munir, Munir; Ariyani, Amra (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This research aims to assess the effectiveness of the Edpuzzle interactive video platform in enhancing the listening abilities of the seventh-grade students of SMPN 1 Sungguminasa. The objective is derived from the issue identified subsequent to the pre-survey, which revealed that the students' listening scores were below the standard. The researcher used the Classroom Action Research (CAR), comprising two cycles, each involving four steps: planning, action, observation, and reflection. Data collection involved observations, pre-tests, post-tests, student feedback and documentation. The researcher chose 38 students of the seventh-grade students of SMPN 1 Sungguminasa. The researchers introduced EdPuzzle, an e-learning platform, to the students. Before the study commenced, both researchers and students practiced using it and shared the first and second-cycle test outcomes via a WhatsApp group. The findings indicated that EdPuzzle positively impacted the listening skills of the seventh-grade students of SMPN 1 Sungguminasa. This was evident in the average test score increase from the post-tests, showing a rise of 20% in cycle 1 and 71% in cycle II.